The association between gut microbiome and PCOS: evidence from meta-analysis and two-sample mendelian randomization - Min, Qiusi; Geng, Hongling; Gao, Qian; Xu, Min (Frontiers in Microbiology, 2023)
Background: Observational studies and clinical experimentation has indicated a link between the gut microbiotas(GMs) and polycystic ovary syndrome (PCOS)，however, the causality and direction of causality between gut microbiome and PCOS remains to be established. Methods:We conducted a comprehensive search of four databases up until June 1, 2023, and subjected the results to a meta-analysis.A bidirectional two-sample Mendelian randomization (MR) analysis was employed to investigate the impact of gut microbiota on polycystic ovary syndrome (PCOS). The genome-wide association study (GWAS) data for PCOS comprised 113,238 samples, while the GWAS data for gut microbiota were derived from the MiBioGen consortium, encompassing a total sample size of 18,340 individuals. Single nucleotide polymorphisms (SNPs) were selected as instrumental variables at various taxonomic levels, including Phylum, Class, Order, Family, and Genus. The causal associations between exposures and outcomes were assessed using four established MR methods. To correct for multiple testing, the false discovery rate (FDR) method was applied. The reliability and potential biases of the results were evaluated through sensitivity analysis and F-statistics.Results: The meta-analysis incorporated a total of 20 studies that met the criteria, revealing a close association between PCOS and specific gut microbiota species. As per the results from our MR analysis,In our study, we identified six causal associations between the gut microbiome and polycystic ovary syndrome (PCOS). At the genus level, Actinomyces (ORIVW = 1.369, FDR=0.040), Streptococcus (ORIVW =1.548, FDR = 0.027), and Ruminococcaceae UCG-005 (ORIVW =1.488, FDR = 0.028) were identified as risk factors for PCOS. Conversely, Candidatus Soleaferrea (ORIVW= 0.723, FDR = 0.040), Dorea (ORIVW =0.580, FDR = 0.032), and Ruminococcaceae UCG-011 (ORIVW = 0.732, FDR = 0.030) were found to be protective factors against PCOS. Furthermore, the MR-PRESSO global test and MR-Egger regression indicated that our study results were not affected by horizontal pleiotropy (P > 0.05). Finally, the leave-one-out analysis corroborated the robustness of the MR findings.Conclusion: Both our meta-analysis and MR study indicatesOur MR study demonstrates that there is a causal relationship between the gut microbiome and PCOS, which may contribute to providing novel insights for the development of new preventive and therapeutic strategies for PCOS.